Positive psychology across the lifespan an existential perspective - Worth, Piers (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2022)
"Positive Psychology Across the Life Span provides an insight into how we are affected by the different stages of adult development and gives us the opportunity to change through choice rather than leaving change to chance. The science of positive psychology offers a wealth of research and evidence-based interventions and shares insights into which habits and behaviours contribute to how to live a flourishing life. This book aims to extend that knowledge by introducing and incorporating key aspects of existential and humanistic psychology and explores positive psychology with a life-span perspective. It goes beyond theory to look at practical application, with insightful reflective questions. Whilst acknowledging the differences and disagreements between some of the key figures in the subject areas of the book it seeks to highlight the areas where there is agreement and congruence which have been previously overlooked or ignored. The book will be essential reading for students and practitioners of positive psychology, as well as other mental health professionals"--Provided by publisher.
Introduction: positive psychology across the lifespan: an existential perspective / Piers Worth and Andrew Machon -- Change in and over time: our journey of development - lifespan developmental perspectives of change / Piers Worth -- Our unfolding journey of growth / Piers Worth and Andrew Machon -- The journey's hero: birth of an existential self / Lee Newitt -- Our symbolic journey - heroes or heroines? / Diane Herbert -- The relational context of change / Andrew Machon -- An introduction to the trans-theoretical model of change / Piers Worth -- Developing insight / Andrew Machon -- Existential positive psychology intervention / Piers Worth and Lesley Lyle -- Revisiting positive psychology across the lifespan: an existential perspective / Piers Worth, Andrew Machon and Lesley Lyle.
Includes bibliographical references and index.
Keywords: Positive psychology; Developmental psychology